1999
DOI: 10.1155/1999/536394
|View full text |Cite
|
Sign up to set email alerts
|

The AgNOR Quantity as Prognostic Parameter in Choroidal Melanomas: A Standardised Analysis

Abstract: In order to assess the prognostic significance of silver‐stained nucleolar organizer region (AgNOR) proteins, a standardised analysis has been performed on 34 ocular globes with choroidal melanomas. On formalin‐fixed paraffin‐embedded sections, the visualisation and quantification of AgNORs were achieved according to the guidelines of the Committee on AgNOR Quantification (1995); statistical analysis was performed on the mean AgNOR area values (NORA). We have encountered significantly higher NORA values in non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…They are also associated with a significantly higher risk of cancer-specific death. NORA proved to be an independent prognostic factor for survival (41).…”
Section: Clinical Parametermentioning
confidence: 93%
See 1 more Smart Citation
“…They are also associated with a significantly higher risk of cancer-specific death. NORA proved to be an independent prognostic factor for survival (41).…”
Section: Clinical Parametermentioning
confidence: 93%
“…Tissues with high cellular proliferation usually show a more intense reaction, due to a high content of B23 and nucleolin during the S-G2-phase, with their respective low contents during the G1 phase. (40) standardised method for evaluating silver-stained NOR (AgNOR) in order to determine the prognosis in uveal melanoma (41). As a result of the surface area calculations of AgNOR, the mean AgNOR area (NORA) can be computed.…”
Section: Clinical Parametermentioning
confidence: 99%
“…These silver-stained nucleolar organizer region (AgNOR) proteins are associated with ribosomal genes, and their quantity has been demonstrated to be strictly related to the rapidity of cell proliferation (Derenzini et al 1989;Derenzini et al 1990;Öfner et al 1992). Furthermore, studies concerning this histochemical method have shown the prognostic value of AgNOR quantity as an independent variable, able to predict the recurrences and/or the overall survival in various kinds of malignancies as well as of skin tumors (Egan et al 1988;Rüschoff et al 1990;Delahunt et al 1991;Eusebi et al 1991;De Rosa et al 1992;Pich et al 1992;Aubele et al 1994;Pich et al 1994;Öfner et al 1995b;Antonangelo et al 1997;Giuffrè et al 1998;Tuccari et al 1999;Giuffrè et al 2001;Giuffrè et al 2006). Moreover, in a previous study , we applied for the first time the standardized procedure proposed by the European Committee on AgNOR Quantification (Öfner et al 1995b) to determine the AgNOR quantity in the different stages of actinic keratosis, thus identifying those cases with proliferative characteristics and a strong propensity to develop infiltrative SCC (Tuccari et al 2001); we concluded that in AK a progressively increased cell cycle speed proceeded in the meantime the epithelial dysplasia appears and it is extended to the different layers of the epidermis (Tuccari et al 2001).…”
mentioning
confidence: 99%